2014
DOI: 10.4274/jcrpe.1524
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Passive Smoking on the Six-Minute Walk Test in Obese Pediatric Cases

Abstract: Objective: The aim of this study was to evaluate whether exposure to second-hand smoke affected the six-minute walk test (6MWT) of obese non-asthmatic pediatric cases.Methods: Obese pediatric patients (body mass index >95th p) with no existing co-morbidities were included in the study. Smoke exposure was assessed with a self-reported questionnaire completed by the parents. The subjects were divided into two groups: Group 1 consisting of obese children exposed to passive smoking and Group 2 of obese children no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although no prior research has yet examined the impact of SHS exposure on children’s laboratory measured VO 2peak , the results are in line with Magnússon et al [ 38 ], who have found children’s CRF (measured by maximal cycle ergometer test) to be significantly reduced for those with smoking parents. Kaymaz et al [ 40 ] have also shown that children exposed to parental smoking have reduced performance on the six-minute walk test. The mechanism by which SHS exposure reduces VO 2peak cannot be determined from the present study, but key components of tobacco smoke such as CO and particulate matter have each been shown to individually impact CRF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no prior research has yet examined the impact of SHS exposure on children’s laboratory measured VO 2peak , the results are in line with Magnússon et al [ 38 ], who have found children’s CRF (measured by maximal cycle ergometer test) to be significantly reduced for those with smoking parents. Kaymaz et al [ 40 ] have also shown that children exposed to parental smoking have reduced performance on the six-minute walk test. The mechanism by which SHS exposure reduces VO 2peak cannot be determined from the present study, but key components of tobacco smoke such as CO and particulate matter have each been shown to individually impact CRF.…”
Section: Discussionmentioning
confidence: 99%
“…For children and young people, research is limited. Of the research that exists, studies have found children’s CRF (measured by maximal cycle ergometer test) to be significantly reduced for those with smoking parents [ 38 ], adolescents exposed to SHS to have increased systolic blood pressure whilst exercising [ 39 ], and obese children exposed to SHS were found to have reduced performance on a six-minute walk test [ 40 ]. PA has been shown to reduce adolescent smoking uptake [ 41 ] and aid cessation [ 42 ], but there is limited research exploring the association between SHS exposure, or having a smoking family member, on children’s engagement in PA. Further research is therefore required to examine the association between SHS exposure, cardiorespiratory fitness, and PA in children.…”
Section: Introductionmentioning
confidence: 99%
“…Exposed children are at increased risk of chronic airway inflammation, lung function defects [ 45 ], severe asthma attacks, respiratory infections, ear infections, sudden infant death syndrome [ 46 ], and increased risk of hospitalisation in asthmatics [ 47 ]. The negative health effects of SHS exposure have physiological implications for PA and CRF, with SHS exposure associated with reduced exercise performance [ 48 , 49 , 50 ] and increased blood pressure in exercising adolescents [ 51 , 52 ]. Children from smoking households could therefore be at greater risk of low fitness and the associated health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…As a submaximal exercise test, the 6-minute walking test (6MWT) can be a suitable index for the exercise capacity of patients with respiratory problems [1,2]. The 6MWT is a simple and inexpensive test that provides the global and integrated response of pulmonary and nonpulmonary factors [3,4].…”
Section: Introductionmentioning
confidence: 99%